Pengaruh Pengembangan Karir dan Worklife balance terhadap Kepuasan Kerja Pada Karyawan Produksi Departemen Speaker PT X - Sari Cipta Ningrum; Ety Nurhayaty (Jurnal Visi Manajemen, 2025)
Job satisfaction is a crucial indicator in achieving optimal employee performance. Satisfied employees tend to be more productive and perform better in their roles. Various factors affect job satisfaction, including career development and work-life balance. Career development provides direction and motivation for employees to reach higher career levels, enhancing their sense of achievement and attachment to their work. Meanwhile, work-life balance plays an essential role in maintaining a balance between work responsibilities and personal life. A good balance helps prevent stress, burnout, and improves overall employee well-being. This study aims to examine the impact of career development and work-life balance on job satisfaction among production employees in the Speaker Department at PT X. The research used a quantitative method with a causal associative approach. Total sampling was applied, involving 71 respondents from the department. Data were collected through direct observation and questionnaires focusing on employees' perceptions of career development and their work-life balance. The collected data were analyzed using SPSS version 23 with various statistical tests, including validity, reliability, classical assumption tests, multiple linear regression, t-tests, f-tests, and the coefficient of determination. The results showed that both career development and work-life balance positively and significantly influence job satisfaction, both partially and simultaneously. These two factors collectively impact the job satisfaction levels of employees in the company. These findings offer strategic insights for human resource management, which can be used to design better policies that support employee satisfaction and performance.